2015
DOI: 10.1038/srep17949
|View full text |Cite
|
Sign up to set email alerts
|

RNAi mediated inhibition of viroid infection in transgenic plants expressing viroid-specific small RNAs derived from various functional domains

Abstract: Previous attempts to develop RNAi-mediated viroid-resistant transgenic plants using nearly full-length Potato spindle tuber viroid (PSTVd) hairpin RNA (hpRNA) were successful; however unusual phenotypes resembling viroid infection occurred. Therefore, in the present work, transgenic Nicotiana benthamiana lines expressing both partial and truncated versions of PSTVd hpRNA were developed. Specifically, seven partial or truncated versions of PSTVd sequences were selected according to the hotspots of both PSTVd-sR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 39 publications
(64 reference statements)
0
19
0
1
Order By: Relevance
“…Profiling of vd-sRNA revealed that certain regions of the PSTVd genome produced more sRNAs than others, that is to say, they are vd-sRNA producing hotspots (produces more than 10% of sRNA) while less vd-sRNA producing regions on viroids are called as non-hotspots (produces less than 10% of sRNA; Fig. 1A ); for details see refs 16 , 20 and 21 . In order to investigate the possible vd-sRNA derived from the PSTVd variants binding to 3′ UTR targets in tomato transcriptome datasets, the 21-nt long vd-sRNA were then analyzed using the psRNATarget web-based tool 22 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Profiling of vd-sRNA revealed that certain regions of the PSTVd genome produced more sRNAs than others, that is to say, they are vd-sRNA producing hotspots (produces more than 10% of sRNA) while less vd-sRNA producing regions on viroids are called as non-hotspots (produces less than 10% of sRNA; Fig. 1A ); for details see refs 16 , 20 and 21 . In order to investigate the possible vd-sRNA derived from the PSTVd variants binding to 3′ UTR targets in tomato transcriptome datasets, the 21-nt long vd-sRNA were then analyzed using the psRNATarget web-based tool 22 .…”
Section: Resultsmentioning
confidence: 99%
“…PSTVd is a good model for studying viroid-host interactions, as it is a widely-studied viroid 12 , 14 . For example, previously it has been used to demonstrate the viroid’s (i) structure in solution by high-throughput selective 2′-hydroxyl acylation analyzed by primer extension (SHAPE) 3 , (ii) cell-to-cell trafficking through plasmodesmata and its systemic movement through phloem 15 , (iii) role of vd-sRNA in different host species such as tomato and Nicotiana species 11 13 , and, (iv) to develop viroid resistant plants 16 , 17 . It has also been used to monitor tomato gene regulation by microarray analysis and its effect on tomato miRNA expression 9 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The error bars indicate SD. different regions of PSTVd failed to confer resistance against viroid infection [22]. In this scenario, understanding the relationship between the viroid genome and that of host defense genes are of the utmost important as this can provide a clue towards designing novel strategies against viroid infection.…”
Section: Discussionmentioning
confidence: 99%
“…Although an RNA silencing-based strategy presents a very attractive method with which to create viroid-resistant/tolerant plants, transgenic tomato and N. benthamiana plants expressing PSTVd-specific small RNAs (PSTVd-sRNA) failed to resist PSTVd infection [21,22]. Hence, an understanding of the viroids host defense genes are of the utmost importance in the development of alternative viroid resistant strategies.…”
Section: Introductionmentioning
confidence: 99%
“…RNA-based resistance to viroids (reviewed in Dalakouras et al, 2015) was initially achieved through the transgenic expression of antisense RNAs (Matousek et al, 1994), hammerhead ribozymes (Atkins et al, 1995;Carbonell et al, 2011;Yang et al, 1997) or dsRNA ribonucleases (Sano et al, 1997). Later, RNA silencing-based strategies showed that antiviroid resistance could be obtained through the co-inoculation of large amounts of dsRNA molecules of viroid sequence (Carbonell et al, 2008), or through the expression of constructs producing hairpin RNAs of viroid sequence (Adkar-Purushothama et al, 2015;Carbonell et al, 2008;Schwind et al, 2009). Despite their effectiveness, these potent approaches have major limitations, such as the lack of high specificity or the tediousness of the generation of hairpin constructs or of large amounts of dsRNAs.…”
mentioning
confidence: 99%